Ion Mobility—Mass Spectrometry-Based Screening for Inhibition of α-Synuclein Aggregation. Issue 3 (June 2015) - Liu, Yanqin; Graetz, Michael; Ho, Lam; Pukala, Tara L.
Aberrant protein folding and formation of amyloid fibrils are associated with numerous debilitating human diseases, for which there are currently no suitable therapeutic treatments. For instance, Parkinson's disease is characterised pathologically by the intraneural accumulation of the amyloid protein α -synuclein. In order to search for new therapeutic agents that are effective in preventing the early conformational changes that precede protein aggregation, it is necessary to devise new analytical screening approaches. Here we demonstrate the use of ion mobility–mass spectrometry for screening of molecules capable of inhibiting the misfolding and aggregation of α -synuclein (specifically, the A53T human mutant). Importantly, this assay allows for the analysis of conformational changes that precede aggregation, and therefore is unique in its ability to identify inhibitors working at the earliest stages of amyloid formation. In addition, we use complementary mass spectrometry methods to probe selected protein–ligand interactions responsible for fibril inhibition.